Hubungan Tingkat Kecemasan dengan Intensitas Nyeri Persalinan pada Ibu Bersalin Kala I di Puskesmas Gemolong - Mutia Fatika Rahmat; Kamidah . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Background: Labor pain is influenced by physiological and psychological factors, including pregnancy-related anxiety. High anxiety may increase pain perception during labor through sympathetic nervous system activation. Evidence regarding the relationship between pregnancy-related anxiety and labor pain intensity in primary healthcare settings remains limited. Objective: To determine the relationship between anxiety level and labor pain intensity among women in the first stage of labor at Gemolong Community Health Center. Methods: A quantitative cross-sectional study was conducted among 30 women in the first stage of labor selected through consecutive sampling. Anxiety was measured using the Pregnancy Related Anxiety Questionnaire-Revised 2 (PRAQ-R2), while labor pain intensity was assessed using the Numeric Rating Scale (NRS). Data were analyzed using Spearman's rank correlation test. Results: Most respondents experienced moderate anxiety (66.7%) and severe labor pain (63.3%). A significant relationship was found between anxiety level and labor pain intensity (p=0.001; r=0.579). Conclusion: Anxiety level was significantly associated with labor pain intensity during the first stage of labor. Anxiety screening during pregnancy should be strengthened as part of comprehensive maternity care.